2012
DOI: 10.1111/j.1743-6109.2011.02597.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual Behavior and Oral Contraception: A Pilot Study

Abstract: Introduction Oral contraceptives (OCs) induce mood and libido changes. Aim The aim of this study was to evaluate in young, eumenorrheic, healthy women the sexual behavior and the genital vascular effects of an OC containing 30 µg ethinylestradiol (EE) and 3 mg drospirenone (DRSP). Main Outcome Measures The main outcome measures are McCoy Female Sexuality Ques… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 34 publications
(62 reference statements)
1
38
0
Order By: Relevance
“…We found that more women using CHC containing anti-androgenic progestin reported sexual problems and sexual distress than women using CHC containing other progestins. Consistent with our results, Battaglia et al (2012) , in an interventional study of 22 women, reported an increase in pain and a decrease in sexual function, measured using the McCoy Female Sexuality Questionnaire, after 3 months with a CHC containing an anti-androgenic progestin (Battaglia et al 2012). In contrast, Wallwiener et al (2010) found no difference in full-scale FSFI score between women using CHC containing androgenic or anti-androgenic progestins in a cross-sectional setting, and Davis et al (2013) found equal improvement in FSFI Desire and Arousal domain scores in women randomized to CHCs containing either androgenic or anti-androgenic progestin (Davis et al 2013;Wallwiener et al 2010b).…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…We found that more women using CHC containing anti-androgenic progestin reported sexual problems and sexual distress than women using CHC containing other progestins. Consistent with our results, Battaglia et al (2012) , in an interventional study of 22 women, reported an increase in pain and a decrease in sexual function, measured using the McCoy Female Sexuality Questionnaire, after 3 months with a CHC containing an anti-androgenic progestin (Battaglia et al 2012). In contrast, Wallwiener et al (2010) found no difference in full-scale FSFI score between women using CHC containing androgenic or anti-androgenic progestins in a cross-sectional setting, and Davis et al (2013) found equal improvement in FSFI Desire and Arousal domain scores in women randomized to CHCs containing either androgenic or anti-androgenic progestin (Davis et al 2013;Wallwiener et al 2010b).…”
Section: Discussionsupporting
confidence: 78%
“…The reported negative effects of OC on sexual function have mainly been on desire and sexual thoughts, but some reports describe negative effects on lubrication and pain (Battaglia et al 2012; Davis and Castano 2004). Research on OC effects on sexuality show varied results with reports of both improved and worsened sexual function correlated to OC.…”
Section: Introductionmentioning
confidence: 99%
“…In some studies the EE/DRSP COC used has been shown to improve the MDQ domains Water retention and Negative affect [40][41][42], but this was not observed in our study. Several publications report positive effects of EE/DRSP COCs on mood and sexual function [40][41][42][43][44][45], whereas others report negative effects [1,2].…”
Section: Discussionmentioning
confidence: 99%
“…Only a few studies report combined investigations of the effect of COCs on androgens and the occurrence of behavioral side effects and those studies also report conflicting results [1,2,5,27,[46][47][48][49][50][51]. Potential reasons for these inconsistences include differences in subject characteristics such as age, BMI, genetic factors including individual sensitivities to androgen reduction, and differences in study design such as endpoints, type of oral contraception and duration of treatment [3,5,15,27].…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
See 1 more Smart Citation